Analyzing Safety Management Practices affecting Safety Performance in the Electrical Industry: A Systematic Review - Tawfeeq, Omar Munaf; Thiruchelvam, Sivadass A. L.; Abidin, Izham Bin Zainal (Engineering, Technology & Applied Science Research, 2024)
Workplace accidents can be avoided through meticulous planning, systematic organization, and through evaluating the efficacy of implemented control measures. Acquiring high standards in a safety management system can be achieved using models that facilitate the execution of proactive steps to mitigate work-related risks. This study aimed to ascertain the presence of effective safety practices throughout the implementation of safety performance measures. A systematic literature review was carried out following the guidelines provided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Thirty articles in English, published between 2010 and 2020, were identified by a comprehensive search in the Scopus, Science Direct, and Web of Science databases, based on certain criteria. The results demonstrated the efficacy of safety management practices and their impact on safety performance. The predominant focus of the evaluations was procedural safety, with relatively little emphasis placed on the elements of human safety that were significantly overlooked.